A red phosphorus-loaded carbon fiber material and application thereof in preparation of potassium ion batteries

CN119877200BActive Publication Date: 2026-10-23LANZHOU JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510305293.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2026-10-23
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

这些多磷化物与溶剂通过强相互作用结合,导致穿梭效应,进而引发活性磷的损失及电极腐蚀等一系列问题

Benefits of technology

本发明利用蒸发-冷凝法将红磷引入碳纳米纤维膜的孔隙中,得到负载铁金属团簇的红磷负极材料,通过将红磷纳米化并嵌入多孔碳纤维基体,有效克服了红磷的大体积变化问题;同时,利用同轴静电纺丝技术简化了活化工艺,并引入金属团簇显著提升了红磷负极的储钾电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877200B_ABST
    Figure CN119877200B_ABST
Patent Text Reader

Abstract

The application specifically relates to a red phosphorus-loaded carbon fiber material and application in preparation of a potassium ion battery. The method comprises the following steps: preparing a shell solution by dissolving polyacrylonitrile, iron acetylacetone and ZIF-8 in N,N-dimethylformamide; dissolving potassium hydroxide in dimethyl sulfoxide to obtain a core solution; spinning the shell solution and the core solution into a nanometer composite fiber membrane through coaxial electrospinning; performing pre-oxidation and carbonization treatment on the nanometer composite fiber membrane to obtain a uniform porous carbon nanofiber membrane loaded with iron metal clusters under a proper atmosphere and temperature; and introducing red phosphorus into the pores of the carbon nanofiber membrane by using an evaporation-condensation method to obtain a red phosphorus anode material loaded with iron metal clusters. The red phosphorus is nanometerized and embedded in a porous carbon fiber matrix, so that the volume change problem of the red phosphorus is effectively overcome; meanwhile, the coaxial electrospinning technology is used to simplify the activation process, and the introduction of metal clusters significantly improves the potassium storage electrochemical performance of the red phosphorus anode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of potassium-ion battery anode material technology, specifically to a carbon fiber material loaded with red phosphorus, a method for preparing the material, and the application of the material as an anode in the preparation of potassium-ion batteries. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Potassium-ion batteries (KIBs) are considered a potential alternative to lithium-ion batteries (LIBs) due to their high energy density and cost-effectiveness, especially for large-scale energy storage. However, potassium-ion (K) batteries... + The relatively large ionic radius (1.38 Å) of KIBs results in slow migration during insertion / extraction, accelerating electrode material breakage and severely limiting the practical application of KIBs. Therefore, one of the primary challenges for KIBs is the development of reliable electrode materials, especially anode materials with stability, high activity, and good structural strength.

[0004] Red phosphorus (Red P), as an inexpensive anode material, exhibits extremely high theoretical capacity based on alloying / alloying mechanisms and appropriate redox potentials, showing the potential to achieve ultra-high energy densities. However, red phosphorus has low electrical conductivity (10⁻⁶ Ω·cm). - 14 S cm -1 ) and its K + The volume expansion during insertion / extraction severely affects its cycling stability, making it difficult to meet practical application requirements. Furthermore, the energy storage mechanism of red phosphorus is similar to that of sulfur, generating polyphosphoric acid molecules during the reaction. These polyphosphoric acids bind to the solvent through strong interactions, leading to a shuttle effect and subsequently causing a series of problems such as loss of active phosphorus and electrode corrosion.

[0005] Therefore, designing and preparing a porous carbon matrix that can effectively accommodate red phosphorus nanoparticles to alleviate the volume expansion effect is of great scientific significance and practical value for improving the potassium storage electrochemical performance of red phosphorus anodes. Summary of the Invention

[0006] To address the current shortcomings of activating pore-forming agents in achieving uniform action on flexible fiber membranes, this invention provides a coaxial electrospun self-supporting anode material applicable to potassium-ion batteries. This material, based on a simple one-step sintering method, can rapidly and effectively prepare a uniform microporous structure on the surface of carbon materials, providing a stable loading space for red phosphorus nanoparticles and possessing the potential for large-scale industrial production.

[0007] Based on the above effects, the present invention provides the following technical solution: In a first aspect, the present invention provides a carbon fiber material loaded with red phosphorus, wherein the material uses a self-supporting flexible composite carbon fiber membrane as a matrix, and red phosphorus is loaded into the carbon fiber membrane through physical adsorption and chemical surface reaction.

[0008] The aforementioned carbon fiber material is first obtained by electrospinning to create a matrix carbon fiber material, making it a self-supporting, flexible material that can be arbitrarily cut to suit various work requirements. Furthermore, the carbon fiber membrane prepared by spinning possesses a rich porous structure. This structure not only enhances its electrochemical performance as a potassium ion anode but also provides abundant attachment sites for red phosphorus loading. Addressing the shortcomings of red phosphorus, such as low conductivity and polyphosphide dissolution, this invention achieves excellent rate performance and long cycle life through an optimized strategy of red phosphorus-carbon fiber membrane material composite. The initial capacity is above 600 mAh / g, and the capacity retains more than 50% after 200 cycles.

[0009] In a second aspect, the present invention provides a method for preparing the carbon fiber material loaded with red phosphorus as described in the first aspect, comprising the following steps: (1) Nanocomposite fiber membranes were prepared by coaxial electrospinning using 2-methylimidazolium zinc salt (ZIF-8), iron salt, and polymer dissolved in N,N-dimethylformamide as the shell solution and alkaline dimethyl sulfoxide as the core solution. (2) The nanocomposite fiber membrane prepared in step (1) is sintered in an oxygen-isolated environment to obtain a porous carbon nanofiber membrane. (3) The porous carbon nanofiber membrane prepared in step (2) is heated and annealed together with red phosphorus in a vacuum environment to obtain the final product.

[0010] In step (1), the following preferred solutions are available: The iron salt is preferably an organic iron compound. In one embodiment of the present invention, the iron salt is iron acetylacetonate. The polymer is preferably a polymer that can be used to prepare flexible spinning materials, including but not limited to polyester, polyamide, polyvinyl alcohol, polyacrylonitrile, etc.

[0011] In one embodiment verified by the present invention, the shell solution is prepared as follows: 0.20~0.30g ZIF-8, 0.07~0.15g ferric acetylacetone, and 1.00~1.50g polyacrylonitrile are dissolved in 8~15ml N,N-dimethylformamide and then fully dispersed to obtain the shell solution.

[0012] The nucleus solution is preferably prepared by mixing an inorganic base with dimethyl sulfoxide. The inorganic base may be sodium hydroxide, potassium hydroxide, or calcium hydroxide. In one embodiment verified by the present invention, the inorganic base is potassium hydroxide. The nucleus solution is prepared as follows: 0.35~0.60g of potassium hydroxide is added to 8~15ml of dimethyl sulfoxide and heated at 55~65℃ for 10~12 days until it is completely dissolved.

[0013] The coaxial electrospinning is performed by coaxially arranged inner and outer needles. The outer needle is connected to the shell solution, with an inner diameter of 0.95~1.10 mm and an outer diameter of 1.4~2.0 mm. The inner needle is connected to the core solution, with an inner diameter of 0.3~0.5 mm and an outer diameter of 0.6~0.8 mm. The propulsion speed of the shell solution and the core solution is 0.06~0.10 mm / min, the lateral translation speed is 280~350 mm / min, the roller receiving speed is 8~15 r / min, and the open circuit voltage is positive 13~17 KV and negative -3~-1 KV.

[0014] In step (2) above, the sintering procedure is as follows: the nanocomposite fiber membrane is heated to 210~250℃ and held for 3~4 h, then placed in an argon atmosphere and heated to 860~920℃ at a rate of 4~6℃ / min, and sintered for 1.8~3 h to obtain a porous carbon nanofiber membrane. The nanocomposite fiber membrane is subjected to high-temperature heat treatment in an argon atmosphere, the central atoms of the ZIF-8 metal framework in the shell layer volatilize to form a macroporous structure, iron acetylacetone is reduced to iron metal clusters, and the potassium hydroxide activator in the core layer can generate a large number of micropores in the internal structure of the fiber, thus obtaining a hierarchical porous flexible carbon fiber material with metal clusters loaded on it.

[0015] In step (3) above, red phosphorus is infiltrated into the pores of carbon material through evaporation and condensation, ultimately obtaining a three-dimensional porous carbon nanofiber-supported red phosphorus nanoparticle composite material modified with iron metal clusters. The mass ratio of the porous carbon nanofiber membrane to red phosphorus is 1:1.5~3, with a more preferred ratio of 1:2. The heating and annealing process is as follows: the porous carbon nanofiber membrane and red phosphorus are encapsulated together in a vacuum quartz tube, heated to 850~900℃ at 8~12℃ / min and held for 7~10 h, then cooled to 250℃ at 0.8~1.5℃ / min, held for 22~26 h, and finally cooled to room temperature to obtain the final product.

[0016] In a third aspect, the present invention provides the application of the above-mentioned carbon fiber material loaded with red phosphorus in the preparation of potassium-ion batteries.

[0017] In a fourth aspect, the present invention provides a negative electrode for a potassium-ion battery, wherein the negative electrode is a carbon fiber material loaded with red phosphorus as described in the first aspect.

[0018] In a fifth aspect, the present invention provides a potassium-ion battery having the negative electrode described in the fourth aspect.

[0019] In one specific embodiment, the potassium-ion battery described above is a button cell, and the assembly method is as follows: the material described in the first aspect is used as the negative electrode, potassium metal is used as the positive electrode, glass fiber is used as the separator, and potassium bis(fluorosulfonyl)imide (KFSI) in ethylene carbonate (EC) / diethyl carbonate (DEC) solution is used as the electrolyte; in the electrolyte, the volume ratio of EC to DEC is 1:0.8~1.2, and the concentration of KFSI is 3.5~4.5 mol / L.

[0020] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes an evaporation-condensation method to introduce red phosphorus into the pores of a carbon nanofiber membrane, thereby obtaining a red phosphorus anode material loaded with iron metal clusters. By nano-sizing red phosphorus and embedding it into a porous carbon fiber matrix, the problem of large volume change of red phosphorus is effectively overcome. At the same time, the activation process is simplified by using coaxial electrospinning technology, and the introduction of metal clusters significantly improves the potassium storage electrochemical performance of the red phosphorus anode. Attached Figure Description

[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0022] Figure 1 The morphology characterization results are for the red phosphorus carbon fibers loaded in Example 1; in, Figure 1 A is a planar SEM image of the carbon material obtained after coaxial electrospinning. Figure 1 B is a cross-sectional SEM image.

[0023] Figure 2 The electrochemical performance of the potassium-ion battery assembled in Example 1; Figure 2 (a) The charge-discharge curves of the potassium-ion battery assembled in Example 1 at a current density of 0.1 A / g for the first three cycles; Figure 2 (b) Cycling performance of the potassium-ion battery assembled in Example 1 at a current density of 0.1 A / g; Figure 2 (c) Cycling performance of the potassium-ion battery assembled in Example 1 at a current density of 1 A / g.

[0024] Figure 3 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 1 is shown. Figure 3(a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 1 at a current density of 0.1 A / g for the first three cycles; Figure 3 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 1 at a current density of 0.1 A / g; Figure 3 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 1 at a current density of 1 A / g.

[0025] Figure 4 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 2 is shown. Figure 4 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 2 at a current density of 0.1 A / g for the first three cycles; Figure 4 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 2 at a current density of 0.1 A / g; Figure 4 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 2 at a current density of 1 A / g.

[0026] Figure 5 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 3 is shown. Figure 5 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 3 at a current density of 0.1 A / g for the first three cycles; Figure 5 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 3 at a current density of 0.1 A / g; Figure 5 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 3 at a current density of 1 A / g.

[0027] Figure 6 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 4 is shown. Figure 6 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 4 at a current density of 0.1 A / g for the first three cycles; Figure 6 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 4 at a current density of 0.1 A / g; Figure 6 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 4 at a current density of 1 A / g.

[0028] Figure 7 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 5 is shown. Figure 7 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 5 at a current density of 0.1 A / g for the first three cycles; Figure 7 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 5 at a current density of 0.1 A / g; Figure 7 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 5 at a current density of 1 A / g.

[0029] Figure 8 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 6 is shown. Figure 8 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 6 for the first three cycles at a current density of 0.1 A / g; Figure 8 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 6 at a current density of 0.1 A / g; Figure 8 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 6 at a current density of 1 A / g.

[0030] Figure 9 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 7; Figure 9 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 7 for the first three cycles at a current density of 0.1 A / g; Figure 9 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 7 at a current density of 0.1 A / g; Figure 9 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 7 at a current density of 1 A / g.

[0031] Figure 10 The electrochemical performance of the potassium-ion battery assembled in Comparative Example 8; Figure 10 (a) The charge-discharge curves of the potassium-ion battery assembled in Comparative Example 8 at a current density of 0.1 A / g for the first three cycles; Figure 10 (b) Cycling performance of the potassium-ion battery assembled in Comparative Example 8 at a current density of 0.1 A / g; Figure 10 (c) Cycling performance of the potassium-ion battery assembled in Comparative Example 8 at a current density of 1 A / g. Detailed Implementation

[0032] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0033] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0034] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments. The red phosphorus used in the following embodiments and comparative examples is commercially available red phosphorus, which can be purchased through commercial channels.

[0035] Example 1 This embodiment prepares highly conductive hierarchical porous carbon fibers with iron metal clusters using coaxial electrospinning. Subsequently, red phosphorus is loaded onto the carbon matrix via evaporation and condensation to prepare a red phosphorus anode material suitable for potassium-ion batteries. The specific steps include: (1) Mix 0.25g ZIF-8 and 0.09g acetylacetone iron with 1.05g polyacrylonitrile, then dissolve in 10ml N,N-dimethylformamide and stir until completely dissolved to obtain a shell solution; add 0.42g potassium hydroxide to 10ml dimethyl sulfoxide solution, heat and stir at 60℃ for 10 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle. The coaxial needle includes an inner needle and an outer needle arranged coaxially. The inner needle has an inner diameter of 0.4 mm and an outer diameter of 0.7 mm. The outer needle has an inner diameter of 1.05 mm and an outer diameter of 1.5 mm. The shell solution is connected to the outer needle and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.07 mm / min. The lateral translation speed of the syringe is 300 mm / min. The receiving speed of the roller is 10 r / min. The open circuit voltage is positive 15 KV and negative -2 KV. After electrospinning, a nanocomposite fiber membrane is obtained. (3) The composite fiber membrane was heated to 220°C in a muffle furnace and held for 2 hours. Then it was placed in an argon gas environment and heated to 900°C at 5°C / min for 2 hours to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters. (4) The porous carbon nanofiber membrane and commercial red phosphorus were encapsulated together in a vacuum quartz tube at a mass ratio of 1:2. The mixture was heated to 898 °C at 10 °C / min and kept at that temperature for 8 h. Then the temperature was lowered to 260 °C at 1 °C / min and kept at that temperature for 24 h. Finally, the temperature was lowered to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus anode material.

[0036] The obtained carbon fibers loaded with red phosphorus were characterized and analyzed, such as... Figure 1 As shown, the left image is a planar SEM image of the carbon material obtained after coaxial electrospinning, and the right image is a cross-sectional SEM image. Both images confirm that the material has a nanoscale fiber structure.

[0037] The obtained self-supporting negative electrode material was cut into 10mm wide square pieces and assembled with potassium metal to form a button cell. The cell uses glass fiber as the separator and KFSI dissolved in EC / DEC (volume ratio 1:1) solvent as the electrolyte with a concentration of 4mol / L.

[0038] Figure 2 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 690 mAh / g, which remains at 528 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 402 mAh / g, which remains at 313 mAh / g after 200 cycles.

[0039] Example 2 In this embodiment, another method for preparing a self-supporting flexible carbon fiber composite red phosphorus anode material is provided, comprising the following steps: (1) Mix 0.30g ZIF-8 and 0.15g acetylacetone iron with 1.50g polyacrylonitrile, then dissolve in 15ml N,N-dimethylformamide and stir until completely dissolved to obtain a shell solution; add 0.60g potassium hydroxide to 15ml dimethyl sulfoxide solution, heat and stir at 65℃ for 12 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle. The coaxial needle includes an inner needle and an outer needle arranged coaxially. The inner needle has an inner diameter of 0.5 mm and an outer diameter of 0.8 mm. The outer needle has an inner diameter of 1.10 mm and an outer diameter of 2.0 mm. The shell solution is connected to the outer needle and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.10 mm / min. The lateral translation speed of the syringe is 350 mm / min. The receiving speed of the roller is 15 r / min. The open circuit voltage is positive 17 KV and negative -3 KV. After electrospinning, a nanocomposite fiber membrane is obtained. (3) The composite fiber membrane was heated to 250°C in a muffle furnace and held for 3 hours. Then it was placed in an argon gas environment and heated to 920°C at 6°C / min for 1.8 hours to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters. (4) The porous carbon nanofiber membrane and commercial red phosphorus were encapsulated together in a vacuum quartz tube at a mass ratio of 1:3. The temperature was heated to 900°C at 12°C / min and kept for 7 hours. Then the temperature was lowered to 250°C at 1.5°C / min and kept for 22 hours. Finally, the temperature was lowered to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus anode material.

[0040] Example 3 In this embodiment, another method for preparing a self-supporting flexible carbon fiber composite red phosphorus anode material is provided, comprising the following steps: (1) Mix 0.20g ZIF-8 and 0.07g acetylacetone iron with 1.00g polyacrylonitrile, then dissolve in 8ml N,N-dimethylformamide and stir until completely dissolved to obtain a shell solution; add 0.350g potassium hydroxide to 8ml dimethyl sulfoxide solution, heat and stir at 55℃ for 12 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle. The coaxial needle includes an inner needle and an outer needle arranged coaxially. The inner needle has an inner diameter of 0.3 mm and an outer diameter of 0.6 mm. The outer needle has an inner diameter of 0.95 mm and an outer diameter of 1.4 mm. The shell solution is connected to the outer needle and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.06 mm / min. The lateral translation speed of the syringe is 280 mm / min. The receiving speed of the roller is 8 r / min. The open circuit voltage is positive 13 KV and negative -1 KV. After electrospinning, a nanocomposite fiber membrane is obtained. (3) The composite fiber membrane was heated to 210°C in a muffle furnace and held for 4 hours. Then it was placed in an argon gas environment and heated to 860°C at 4°C / min for 3 hours to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters. (4) The porous carbon nanofiber membrane and commercial red phosphorus were encapsulated together in a vacuum quartz tube at a mass ratio of 1:1.5. The mixture was heated to 850 °C at 8 °C / min and kept at that temperature for 10 h. Then the temperature was lowered to 250 °C at 0.8 °C / min and kept at that temperature for 26 h. Finally, the temperature was lowered to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus anode material.

[0041] Comparative Example 1 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Example 1 is that step (1) is performed as follows: 0.25g ZIF-8 and 1.05g polyacrylonitrile were mixed and dissolved in 10ml N,N-dimethylformamide and stirred until completely dissolved to obtain the shell solution; 0.42g potassium hydroxide was added to 10ml dimethyl sulfoxide solution and heated and stirred at 60℃ for 10 days until the potassium hydroxide dissolved to obtain the core solution.

[0042] Figure 3 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 444 mAh / g, which remains at 358 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 250 mAh / g, which remains at 179 mAh / g after 200 cycles. The material prepared in this example lacks metal cluster components, which leads to the loss of active phosphorus and electrode corrosion, thus affecting cycle performance. The resulting battery capacity is lower than that of Example 1.

[0043] Comparative Example 2 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Example 1 is that step (1) is performed as follows: 0.25g ZIF-8 and 0.09g ferric acetylacetone were mixed with 1.05g polyacrylonitrile and dissolved in 10ml N,N-dimethylformamide. The mixture was stirred until completely dissolved to obtain the shell solution. 0.21g potassium hydroxide was added to 10ml dimethyl sulfoxide solution and heated and stirred at 60℃ for 10 days until the potassium hydroxide dissolved to obtain the core solution.

[0044] Figure 4 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 652 mAh / g, which remains at 489 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 333 mAh / g, which remains at 221 mAh / g after 200 cycles. The material prepared in this example has a low potassium hydroxide activator content, resulting in insufficient pore formation and incomplete penetration of red phosphorus, which affects subsequent battery performance and hinders activation, leading to a lower battery capacity than in Example 1.

[0045] Comparative Example 3 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Example 1 is that step (1) is performed as follows: Mix 0.25g ZIF-8 and 0.09g ferric acetylacetone with 1.05g polyacrylonitrile, then dissolve in 10ml N,N-dimethylformamide and stir until completely dissolved to obtain the shell solution; add 0.63g potassium hydroxide to 10ml dimethyl sulfoxide solution, heat and stir at 60℃ for 10 days until the potassium hydroxide dissolves to obtain the core solution.

[0046] Figure 5 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 562 mAh / g, which remains at 456 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 333 mAh / g, which remains at 312 mAh / g after 200 cycles. The material prepared in this example has a high potassium hydroxide activator content, and the excessively high pore content causes partial collapse of the carbon skeleton, making it difficult to exert an activation effect and affecting subsequent battery performance. The corresponding battery capacity is lower than that of Example 1.

[0047] Comparative Example 4 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Example 1 is that step (1) is performed as follows: Mix 0.25g ZIF-8 and 0.09g ferric acetylacetone with 0.82g polyacrylonitrile, then dissolve in 10ml N,N-dimethylformamide and stir until completely dissolved to obtain the shell solution; add 0.42g potassium hydroxide to 10ml dimethyl sulfoxide solution, heat and stir at 60℃ for 10 days until the potassium hydroxide dissolves to obtain the core solution.

[0048] Figure 6 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 566 mAh / g, which remains at 424 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 316 mAh / g, which remains at 288 mAh / g after 200 cycles. The material prepared in this example has a low polyacrylonitrile content, resulting in insufficient solution viscosity during electrospinning, making filament formation difficult. The fibers also lack mechanical strength and, after carbonization, cannot form a complete porous network structure, thus reducing conductivity and energy storage performance, resulting in a battery capacity lower than that of Example 1.

[0049] Comparative Example 5 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers by coaxial electrospinning is provided. The difference from Example 1 is that step (1) is performed as follows: Mix 0.25g ZIF-8 and 0.09g ferric acetylacetone with 1.29g polyacrylonitrile, then dissolve in 10ml N,N-dimethylformamide and stir until completely dissolved to obtain the shell solution; add 0.42g potassium hydroxide to 10ml dimethyl sulfoxide solution, heat and stir at 60℃ for 10 days until the potassium hydroxide dissolves to obtain the core solution.

[0050] Figure 7 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 392 mAh / g, which remains at 312 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 289 mAh / g, which remains at 233 mAh / g after 200 cycles. The material prepared in this example has a high polyacrylonitrile content, which increases solution viscosity and causes spinning instability. The increased fiber diameter leads to a dense structure after fiber carbonization, suppressing porosity and hindering the loading and performance improvement of red phosphorus, thus affecting subsequent battery performance. The resulting battery capacity is lower than that of Example 1.

[0051] Comparative Example 6 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers via coaxial electrospinning is provided. The difference from Example 1 is that the obtained self-supporting negative electrode material is cut into 10mm wide square sheets and assembled with potassium metal to form a button cell. This cell uses glass fiber as the separator and KFSI dissolved in EC / DEC (volume ratio 1:1) solvent as the electrolyte at a concentration of 1 mol / L.

[0052] Figure 8 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 670.64 mAh / g, which remains at 415 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 287 mAh / g, which remains at 239 mAh / g after 200 cycles. The material prepared in this example has a relatively low electrolyte concentration, resulting in an uneven and non-dense SEI, slower ion transport, and accelerated electrolyte decomposition, which affects subsequent battery performance, leading to a lower battery capacity than in Example 1.

[0053] Comparative Example 7 In this embodiment, another method for preparing highly conductive hierarchical porous carbon fibers via coaxial electrospinning is provided. The difference from Example 1 is that the obtained self-supporting negative electrode material is cut into 10mm wide square sheets and assembled with potassium metal to form a button cell. This cell uses glass fiber as the separator, and KPF6 dissolved in EC / DEC (volume ratio 1:1) solvent as the electrolyte at a concentration of 1 mol / L.

[0054] Figure 9 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 302 mAh / g, which remains at 215 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 360 mAh / g, which remains at 253 mAh / g after 200 cycles. In the battery prepared in this example, the KPF6 electrolyte has lower solubility in the electrolyte solvent compared to the KFSI electrolyte, resulting in a lower potassium ion concentration. Simultaneously, the ion-pairing interaction between F⁻ and SI⁻ ions in the solvent is weaker, which facilitates the free migration of potassium ions. However, the PF6⁻ ions in KPF6 are relatively difficult to form a stable structure at the electrode / electrolyte interface, thus affecting the battery performance. Therefore, the capacity of this battery is lower than that of Example 1.

[0055] Comparative Example 8 This embodiment prepares highly conductive hierarchical porous carbon fibers with iron metal clusters using coaxial electrospinning. Subsequently, red phosphorus is loaded onto the carbon matrix via evaporation and condensation to prepare a red phosphorus anode material suitable for potassium-ion batteries. The specific steps include: (1) Mix 0.25g ZIF-8 and 0.09g acetylacetone iron with 1.05g polyacrylonitrile, then dissolve in 10ml N,N-dimethylformamide and stir until completely dissolved to obtain a shell solution; add 0.42g potassium hydroxide to 10ml dimethyl sulfoxide solution, heat and stir at 60℃ for 10 days to dissolve the potassium hydroxide to obtain a core solution; (2) The shell solution and the core solution are electrospun through a coaxial needle. The coaxial needle includes an inner needle and an outer needle arranged coaxially. The inner needle has an inner diameter of 0.4 mm and an outer diameter of 0.7 mm. The outer needle has an inner diameter of 1.05 mm and an outer diameter of 1.5 mm. The shell solution is connected to the outer needle and the core solution is connected to the inner needle. The pushing speed of the shell solution and the core solution is 0.07 mm / min. The lateral translation speed of the syringe is 300 mm / min. The receiving speed of the roller is 10 r / min. The open circuit voltage is positive 15 KV and negative -2 KV. After electrospinning, a nanocomposite fiber membrane is obtained. (3) The composite fiber membrane was heated to 220°C in a muffle furnace and held for 2 hours. Then it was placed in an argon gas environment and heated to 900°C at 5°C / min for 2 hours to obtain a three-dimensional porous carbon nanofiber membrane loaded with iron metal clusters. (4) The porous carbon nanofiber membrane and commercial red phosphorus were encapsulated together in a vacuum quartz tube at a mass ratio of 1:2. The mixture was heated to 898 °C at 10 °C / min and kept at that temperature for 8 h. Then the temperature was lowered to 260 °C at 1 °C / min and kept at that temperature for 24 h. Finally, the temperature was lowered to room temperature to obtain a self-supporting flexible carbon fiber composite red phosphorus anode material.

[0056] The obtained self-supporting negative electrode material was cut into 10mm wide square pieces and assembled with potassium metal to form a button cell. The cell uses glass fiber as the separator and KPF6 dissolved in EC / DEC (volume ratio 1:1) solvent as the electrolyte with a concentration of 4mol / L.

[0057] Figure 10 The figures show the charge-discharge curves (a) of the assembled potassium-ion battery at a current density of 0.1 A / g for the first three cycles, and the cycle performance (bc) at current densities of 0.1 A / g and 1 A / g. As can be seen from the figures, at a current density of 0.1 A / g, the battery has an initial specific capacity of 491 mAh / g, which remains at 383 mAh / g after 50 cycles. At a current density of 1 A / g, the battery has an initial specific capacity of 253 mAh / g, which remains at 178 mAh / g after 200 cycles. In the battery prepared in this example, the high concentration of KPF6 electrolyte results in a tighter pairing of hexafluorophosphate ions (PF6⁻) with potassium ions (K⁺), leading to a slower ion migration rate. Furthermore, the side reactions between PF6⁻ ions and the electrode material are more significant, resulting in a decrease in the charge-discharge rate and overall performance of the battery. Therefore, its battery capacity is lower than that of Example 1.

[0058] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of red phosphorus-loaded carbon fiber materials in the preparation of potassium-ion batteries, characterized in that, The preparation method of the carbon fiber material loaded with red phosphorus is as follows: (1) Dissolve 0.20~0.30g ZIF-8, 0.07~0.15g iron acetylacetone and 1.00~1.50g polyacrylonitrile in 8~15ml N,N-dimethylformamide and disperse them evenly to obtain a shell solution. Add 0.35~0.60g potassium hydroxide to 8~15ml dimethyl sulfoxide and heat at 55~65℃ for 10~12 days to mix them evenly to obtain a core solution. Coaxial electrospinning is then carried out to prepare nanocomposite fiber membranes. The coaxial electrospinning is performed by coaxially arranged inner and outer needles. The outer needle is connected to the shell solution, with an inner diameter of 0.95~1.10 mm and an outer diameter of 1.4~2.0 mm. The inner needle is connected to the core solution, with an inner diameter of 0.3~0.5 mm and an outer diameter of 0.6~0.8 mm. The propulsion speed of both the shell solution and the core solution is 0.06~0.10 mm / min, the lateral translation speed is 280~350 mm / min, the roller receiving speed is 8~15 r / min, and the open circuit voltage is positive 13~17 kV and negative -3~-1 kV. (2) The nanocomposite fiber membrane obtained in step (1) is sintered in an oxygen-isolated environment to obtain a porous carbon nanofiber membrane; the sintering procedure is as follows: the nanocomposite fiber membrane is heated to 210~250 ℃ and held for 3~4 h, and then placed in an argon environment and heated to 860~920 ℃ at 4~6 ℃ / min, and sintered for 1.8~3 h to obtain a porous carbon nanofiber membrane; (3) The porous carbon nanofiber membrane obtained in step (2) is heated and annealed together with red phosphorus in a vacuum environment to obtain the final product.

2. The application of the carbon fiber material loaded with red phosphorus as described in claim 1 in the preparation of potassium-ion batteries, characterized in that, In step (3), the mass ratio of the porous carbon nanofiber membrane to red phosphorus is 1:1.5~3; the heating and annealing method is as follows: the porous carbon nanofiber membrane and red phosphorus are encapsulated together in a vacuum quartz tube, heated to 850~900℃ at 8~12℃ / min and kept at that temperature for 7~10 h, then cooled to 250℃ at 0.8~1.5℃ / min, kept at that temperature for 22~26 h, and finally cooled to room temperature to obtain the final product.

3. A negative electrode for a potassium-ion battery, characterized in that, The negative electrode includes carbon fiber material loaded with red phosphorus, which is prepared by the preparation method described in any one of claims 1 or 2.

4. A potassium-ion battery, characterized in that, The battery has the negative electrode as described in claim 3.

5. The potassium-ion battery as described in claim 4, characterized in that, The potassium-ion battery is a button cell, assembled as follows: potassium metal is used as the positive electrode, glass fiber is used as the separator, and KFSI EC / DEC solution is used as the electrolyte. In the electrolyte, the volume ratio of EC to DEC is 1:0.8~1.2, and the concentration of KFSI is 3.5~4.5 mol / L.

Citation Information

Patent Citations

  • Surface-activated multi-channel carbon nanofiber and preparation method thereof, composite metal material and battery negative electrode

    CN115172730A

  • Preparation method of porous interconnected hollow carbon nanofiber membrane

    CN117046319A